PERAN KEPEMIMPINAN DALAM MENGHADAPI FAKTOR-FAKTOR PENDORONG PERUBAHAN DI ERA REVOLUSI 4.0 - Irma Septria Mawarni; Nuri Aslami (Transpublika Publisher, 2022)
The world, including one of Indonesia's countries, is currently facing the era of revolution 4.0. A person's success can be seen from the success of the industry that is being developed in this 4.0 era. The success that is owned by a person is also based on the leadership attitude possessed by an identity leader of the company. This study aims to analyze the role of leadership in dealing with the driving factors in the 4.0 revolution era. This type of article is written using qualitative research using literature studies. The literature study carried out in writing this article includes analysis and also studies related to books, articles, journals, or other relevant sources that are continuous with the title. The findings reveal that there are four leadership-type models in facing the 4.0 revolution, including Social Supers, or commitment to do good, Data-Driven Decisives, namely the decision-making process based on data, Disruption Drivers in the form of the courage to make decisions for the long term by considering trends that will occur in the future. Then Talent Champions, which is the process of developing talent or human resources that are ready to use and able to survive disruption.